IMPLEMENTASI METODE AGILE PADA PEMBUATAN E – REPORT LITTLE CLOUD BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNETER - Waliya Rahmawanti; Ari Rosemalatriasari (Asosiasi Dosen Muda Indonesia, 2023)
This website-based E – Report Little Cloud is specifically for the kindergarten level first, with restrictions on several access rights depending on the user who will use it. The output provided from the website-based Little Cloud E-Report is in the form of a report card which can be downloaded independently by the student's guardian at any time. The purpose of making the website-based Little Cloud E-Report is expected to make it easier for teachers in the process of filling out report cards because everything is computerized properly so that it can minimize the time for filling out report cards. In addition, it makes it easier for parents and students to view report cards anywhere and anytime. The Little Cloud e-Report is created using the Agile method. The agile method is a conceptual framework with an iterative and incremental development approach [7]. The programming language used for the creation of the Little Cloud e-Report is PHP, for database management it uses MySql, and this application uses the CodeIgniter framework.